SIGNIFICANCE OF THE RELATIONSHIP BETWEEN PROINFLAMMATORY CYTOKINE GENE POLYMORPHISMS AND PITUITARY FOLLICULOSTELLATE CELLS FOR HUMAN LONGEVITY - Čukuranović Kokoris, Jovana (Journal of Medical Biochemistry, 2026)
Background: The focus of this study was on the analysis of the relationships between polymorphisms of proinflammatory cytokine genes (tumor necrosis factor α-TNF-α; interleukin 6-IL-6; and interleukin1β-IL-1β), morphology of non-endocrine pituitary folliculostellate cells (FS), gender, and age. Methods: The research involved 20 cadavers (10 male and 10 female) divided into two groups: from 51 to 70 years of age (group I) and over 70 years of age (group II). Pituitary glands were collected during routine autopsy. Isolated pituitaries of cadavers of both sexes were prepared using routine histological techniques. On 5-µm-thick pituitary sections, FS cells were immunohistochemically stained using primary polyclonal anti-S100 (1:400) antibody, visualized by DAB, and analyzed by light microscopy at 40x magnification. Stereological analysis was performed using the ImageJ program. The PCR-RFLP method was used for the genotyping of single nucleotide polymorphisms (SNPs) of TNFα, IL-1β and IL-6. Results: The morphology of FS cells in the second age group showed that they were irregularly shaped, more numerous, single or in groups and significantly (p˂0.05) larger (2.23 times) compared to group I. Single nucleotide polymorphism (SNP) analysis showed no correlation between SNPs of the examined genes and FS cell morphology. Conclusions: It was concluded that in humans of both genders the volume density of FS cells increases with age and is not related to gene polymorphisms of TNFα, IL-1β and IL-6.